Keterampilan Menyimak pada Anak Usia Dini Melalui Metode Bercerita - Rena Mianawati; Tuti Hayati; Aam Kurnia (Jurusan Pendidikan Islam Anak Usia Dini UIN Sunan Gunung Djati Bandung, 2019)
Preliminary observations were made on children in B1 RA Persis 250 Cihamerang group that children's language development was not optimal. This proved that there were still obstacles for children who were not able to have listening skills. The purpose of this study was to determine the listening skills of children before and after the storytelling method was applied, and the application of the storytelling method to improve listening skills. The method used is Class Action Research (CAR) which consists of two cycles. PTK methods include: planning, acting, observing, and reflecting. The data collection techniques used are observation, performance, and documentation. The results showed that the listening skills of children before the method of telling stories were obtained with 32.29 with very few categories, while after applying the method of telling stories to cyclic I obtained a value of 52.71 with a less category, the second cycle obtained a score of 78.44 with a good category. The application of the storytelling method to improve listening skills to teacher activities in the first cycle was obtained an average of 71.88% with sufficient criteria, and in the second cycle obtained an average value of 90.63% with very good criteria. Similarly, the results of the analysis of children's activities in the first cycle obtained an average value of 61.88% with sufficient criteria, and in the second cycle obtained an average value of 77.88% with good criteria. Thus the proposed hypothesis is accepted, meaning that the storytelling method can improve children's listening skills.